2013
DOI: 10.1007/s10926-013-9421-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Coordinated and Tailored Return-to-Work Intervention for Sickness Absence Beneficiaries with Mental Health Problems

Abstract: The intervention delayed RTW compared to conventional case management, after accounting for measured confounding. The delayed RTW may be due to either implementation or program failure, or both. It may also reflect the complexity of retaining employees with mental health problems in the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 38 publications
1
60
0
2
Order By: Relevance
“…To illustrate, in Canada and the Netherlands, beneficial effects of a participatory RTW program on workrelated outcomes were found for sick-listed employees with low back pain (42)(43)(44) and on the duration until sustainable RTW of workers without an employment contract and sick-listed due to musculoskeletal disorders (24). Whereas, in line with our findings, no superior (overall) intervention effect on the duration until sustainable RTW was found for Dutch sick-listed employees with a CMD (12), and an adverse effect of a very similar program was found for Danish sickness absence beneficiaries with mental health problems (7). Furthermore, although we selected participants with positive RTW intentions and our analyses were adjusted for possible changes in this intention, findings were inconsistent with the beneficial intervention effect found for a similar subgroup of employees sick-listed due to a CMD with such positive intention at baseline (12).…”
Section: Lammerts Et Alsupporting
confidence: 84%
See 1 more Smart Citation
“…To illustrate, in Canada and the Netherlands, beneficial effects of a participatory RTW program on workrelated outcomes were found for sick-listed employees with low back pain (42)(43)(44) and on the duration until sustainable RTW of workers without an employment contract and sick-listed due to musculoskeletal disorders (24). Whereas, in line with our findings, no superior (overall) intervention effect on the duration until sustainable RTW was found for Dutch sick-listed employees with a CMD (12), and an adverse effect of a very similar program was found for Danish sickness absence beneficiaries with mental health problems (7). Furthermore, although we selected participants with positive RTW intentions and our analyses were adjusted for possible changes in this intention, findings were inconsistent with the beneficial intervention effect found for a similar subgroup of employees sick-listed due to a CMD with such positive intention at baseline (12).…”
Section: Lammerts Et Alsupporting
confidence: 84%
“…Common mental health problems are mild-to-moderate depressive, anxiety, and stress-related complaints, which have also been described as common mental disorders (CMD) (1). The large impact of CMD on society has led to a growing attention in recent literature for the development and evaluation of interventions that aim to promote returnto-work (RTW) of workers on sick leave due to a CMD (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Many of these studies focused on sick-listed employees, ie, workers with an employment contract.…”
mentioning
confidence: 99%
“…However, two studies 51,52,54 did not report improvement in primary outcomes for the intervention groups. Martin et al 54 compared a co-ordinated and tailored return-to-work (CTRW) intervention to conventional case management, and reported that people in the conventional case management group returned to work more quickly than those in the treatment group. It may have been that, as the CTRW intervention was more in-depth, it took longer for employees to work through the different aspects of the intervention and return to work.…”
Section: Case Management Interventions That Were Based In Occupationamentioning
confidence: 99%
“…There have been a of number collaborative care interventions carried out in OH settings, although none in the UK 30,31,[49][50][51][52][53][54] (Table 3). Interventions were generally targeted at specific conditions, including mental health problems such as depression 30,31,49 or musculoskeletal disorders.…”
Section: Case Management Interventions That Were Based In Occupationamentioning
confidence: 99%
See 1 more Smart Citation